An organic barrier explosion-proof porous medium and its preparation method and application in barrier explosion-proof
By using explosion-proof porous materials with components such as polyolefins, a porous medium with honeycomb mesh structure is prepared, which solves the problems of existing materials collapse and high cost, and achieves comprehensive performance with high strength, good explosion-proof effect and low cost.
Patent Information
- Application Number
- CN202410989839.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-23
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-07-23
AI Technical Summary
Existing explosion-proof materials are prone to collapse during use, affecting explosion-proof performance, and are costly. Polypropylene materials are not resistant to aging and flammable, and have insufficient flame retardant performance.
The barrier and explosion-proof porous materials are used with polyolefins, toughening agents, composite antistatic agents, flame retardants, maleic anhydride grafted polypropylene and other components, and the porous medium with honeycomb mesh structure is prepared through high-speed mixing and screw extrusion mechanism.
The high strength, stable mechanical properties of the porous medium, good explosion-proof effect, low vibration test debris and good oil compatibility are achieved, reducing production costs and weight.
Smart Images

Figure BDA0004958554460000101 
Figure BDA0004958554460000111 
Figure BDA0004958554460000112
Abstract
Description
Technical Field
[0001] The invention relates to the field of explosion-proof storage tanks, and in particular to a barrier explosion-proof porous medium and a barrier explosion-proof material. Background Art
[0002] Oil is flammable, explosive, and volatile, and fire and explosion accidents are very likely to occur during production, storage, and transportation. Therefore, barrier and explosion-proof materials have become one of the current research hotspots. Most of the existing barrier and explosion-proof materials are made of aluminum foil with a mesh structure in the form of sheets or balls. This barrier and explosion-proof material is filled in the storage tank, and will collapse after a period of use, affecting the explosion-proof performance. In order to prevent collapse, a frame is formed with aluminum alloy and the explosion-proof material is filled in the frame, which will increase the weight and cost.
[0003] Therefore, in recent years, most of the research on explosion suppression materials at home and abroad has shifted from metal materials to non-metal materials. In particular, organic polymers have excellent comprehensive properties such as high strength, good heat resistance, good corrosion resistance, etc., and are easy to process and low in cost. They are widely used in barrier explosion-proof materials.
[0004] Among them, polypropylene is widely used in barrier explosion-proof, but pure polypropylene has a large shrinkage rate, is not resistant to aging, has low impact strength and poor low-temperature toughness. In addition, polypropylene is a flammable material and is prone to fire accidents during use. Therefore, when using it, flame retardants and reinforcing materials need to be added to the polypropylene substrate for modification. In the application of polypropylene barrier explosion-proof materials, most people only focus on its mechanical properties and flame retardant properties. However, in the AQ-T 3001-2021 technical requirements for barrier explosion-proof of oil (gas) storage tanks in gas stations, in addition to flame retardant properties, volume resistivity, and explosion-proof properties, barrier explosion-proof materials also need to be tested for compatibility and vibration durability. The compatibility of barrier explosion-proof materials and oil products has an important influence on the service life of barrier explosion-proof materials and the quality of gasoline. After polypropylene is processed and formed, there will be burrs, which are easy to cause debris during use, thus affecting the quality of oil products and the life of the machinery. For example, CN201911223574.4, a flame-retardant polypropylene barrier explosion-proof material and its preparation method and application, includes the following ingredients: 70-80 parts of polypropylene, 20-30 parts of halogen-free composite flame retardant, 5-10 parts of compatibilizer, 1-3 parts of synergist and 1-2 parts of antistatic agent, etc., which only involves the study of explosion performance, and no research on volume resistivity, vibration durability and compatibility tests. CN202010426372.6, a circular tubular explosion-proof structure and barrier explosion-proof composite material, although the amount of vibration test debris was studied, its compatibility test results with oil products were not studied, and its vibration test debris amount is difficult to further reduce. In addition, the existing porous organic polymer barrier explosion-proof medium requires a large wall thickness to ensure mechanical properties, and has problems such as poor compatibility and high cost. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the defects of the prior art and provide an organic barrier explosion-proof porous medium and a preparation method thereof and an application in barrier explosion-proofing. The prepared organic barrier explosion-proof porous medium has high strength, stable mechanical properties, is not easy to collapse, has good explosion-proof effect, has low debris volume in vibration testing, has no effect on oil quality when used for a long time, is easy to produce, has high production efficiency and low production cost.
[0006] In order to achieve the above technical objectives, the technical solution adopted by the present invention is:
[0007] A barrier explosion-proof porous material, the components of which are, by weight percentage: 50.0-70.0wt% polyolefin, 5-10wt% toughening agent, 10-35wt% composite antistatic agent, 8-15wt% flame retardant, 1-5wt% maleic anhydride grafted polypropylene, 0-2wt% color powder, 0.5-2wt% lubricant, and 0.1-0.3% antioxidant;
[0008] Further, the polyolefin is one or a combination of polypropylene and polyethylene; preferably polypropylene, which is sourced from one of Sinopec Shanghai M250E, Yanshan Petrochemical B4808, Hanwha Total RB200, Ningbo Formosa Plastics 3003, Daqing Refining and Chemical PPB4228, and ExxonMobil 7032KN. Sinopec Shanghai M250E or ExxonMobil 7032KN is preferred. Experiments have shown that the source of polypropylene raw materials has an important influence on the amount of debris in the vibration test and the compatibility with oil products.
[0009] Furthermore, the toughening agent is a styrene-butadiene copolymer or an ethylene-octene copolymer, preferably an ethylene-octene copolymer.
[0010] Furthermore, the composite antistatic agent is a mixture of one or more of aluminum powder, iron powder, copper powder, silicon dioxide, graphene, carbon fiber, carbon black, and calcium chloride, which is modified by a coupling agent and used in combination with an organic antistatic agent.
[0011] Furthermore, the organic antistatic agent is one or a combination of polyethylene glycol stearate, polyglycerol stearate, dodecyl sulfopropyl betaine, sorbitan monopalmitate, octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate, glycerol monostearyl ester, antistatic agent 1800, and antistatic agent 129V.
[0012] It is preferred that the inorganic antistatic agent and the organic antistatic agent after modification by the coupling agent are mixed and used at a mass ratio of 10 to 15:1. Modifying the inorganic antistatic agent with the coupling agent first can greatly promote the uniform dispersion of the inorganic particles in the organic matrix, and the inorganic antistatic agent can further enhance the mechanical strength of the barrier explosion-proof.
[0013] Furthermore, the flame retardant is one or a mixture of decabromodiphenylethane, antimony trioxide, aluminum hydroxide, magnesium hydroxide, zinc oxide, ammonium polyphosphate, red phosphorus, melamine, and zinc borate, in order to improve the flame retardant performance and high temperature resistance of the barrier explosion-proof material. Furthermore, the flame retardant compound has a better effect.
[0014] Furthermore, maleic anhydride grafted polypropylene was used as a compatibilizer.
[0015] Furthermore, the antioxidant is antioxidant 1076 or antioxidant 1010.
[0016] Furthermore, toner may be added as needed.
[0017] Furthermore, the lubricant is one or a combination of stearic acid monoglyceride, oleic acid amide, polyoxyethylene stearate, and ethylene bis stearic acid amide. The use of lubricants can greatly reduce friction during production and processing, reduce the generation of burrs and burrs, improve fluidity, optimize processing, and thus greatly reduce the amount of vibration test debris. Oleic acid amide is preferred, and the performance obtained is the best.
[0018] The barrier explosion-proof porous material of the present invention is used to prepare a barrier explosion-proof porous medium, and the barrier explosion-proof porous medium is a honeycomb mesh structure.
[0019] The honeycomb holes of the honeycomb mesh structure can have a variety of shapes, and the projection along the hole depth direction can be one of a circle, triangle, square, rectangle, hexagon, octagon, etc., which is not limited here. Preferably, the honeycomb holes of the honeycomb mesh structure are hexagonal in their axial projection, which is convenient for extruder processing and reduces the difficulty of process processing. The diameter of the inscribed circle of the porous medium is 30 to 40 mm. The length of each hexagon inside the honeycomb is 3.8 to 4.2 mm; the wall thickness is 0.2 to 0.4 mm; the distance between the parallel opposite sides of each hexagon is 6 to 7 mm.
[0020] The preparation method of barrier explosion-proof porous medium is as follows:
[0021] S1. Mix polyolefin, composite antistatic agent, flame retardant and color powder, put them into a high-speed mixer, and stir them evenly at a temperature of 118-125°C;
[0022] S2, then add lubricant and compatibilizer, then heat to 130-150°C, stir evenly, add toughening agent, and continue to stir evenly;
[0023] S3. After stirring, transfer to a screw extruder, the extrusion temperature is 185-200°C, the honeycomb structure mold set at the extruder barrel outlet, the mold temperature is 190-220°C, melt extrusion molding, the extrusion pressure is 10-20Mpa, the extruded pipe is vacuum cooled and shaped, water tank cooled and shaped, pulled, and cut to obtain a barrier explosion-proof porous medium.
[0024] Furthermore, the honeycomb mesh structure may be provided with at least two rows of through holes extending to the center thereof in the circumferential direction, each row of through holes having one or at least two through holes arranged along the axial direction of the honeycomb mesh structure, and the diameter of the through holes is 2.5-5.0 mm.
[0025] The porosity of explosion-proof media with holes on the side is higher than that of porous media without holes on the side. High-porosity media usually have greater energy absorption capacity and can more effectively absorb the energy generated by the explosion, thereby reducing the impact of the explosion. In addition, high porosity can also provide more channels for gas or liquid to diffuse, helping to prevent the explosion from spreading to other areas. By opening holes around the media, the weight of the media can be reduced without affecting the overall performance, which helps to reduce costs and improve convenience. Opening holes can increase the permeability of the media, which helps to diffuse and absorb gas or liquid inside the media, thereby improving explosion-proof performance.
[0026] However, low-porosity media may be more compact and strong, and can better block the pressure and flames generated by the explosion, thereby providing better protection. In addition, low-porosity media may have better durability and stability. You can choose a high-porosity or low-porosity explosion-proof media according to the specific situation. If you need better blocking ability and stability, you can choose a low-porosity media.
[0027] The explosion-proof porous medium of the present invention comprehensively and carefully considers the influence of opening on performance, and adopts measures such as selection of explosion-proof porous materials to ensure the explosion-proof performance of the medium, and can improve the explosion-proof performance without affecting the integrity of the porous explosion-proof medium.
[0028] Compared with the prior art, the beneficial effects of the present invention are as follows: the honeycomb mesh structure of the present invention is extruded by an extruder, which extrude long strips and then cut them into required sizes to obtain a porous medium, which is easy to produce and has low production costs; and the porous medium is made of non-metallic materials, has high strength, is not easy to collapse, and has excellent energy absorption capacity and explosion resistance; furthermore, the surface area of the honeycomb mesh structure is relatively large, which can increase the contact area with the transported natural gas or liquid fuel to achieve a better effect of absorbing explosion energy. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a top view or a front view of the explosion-proof device without openings in the present invention;
[0030] Figure 2 It is a left view of the explosion-proof porous medium with holes opened in the present invention;
[0031] Figure 3 For the tank model;
[0032] Figure 4 This is the mesh division diagram of the tank model;
[0033] Figure 5 The distribution diagram of flame temperature at 1ms under the conditions of air explosion and filling barrier explosion-proof porous medium and the number of through holes in each column t is t=1, t=2, t=3;
[0034] Figure 6 The distribution diagram of flame temperature at 20ms under the conditions of air explosion and filling barrier explosion-proof porous medium and the number of through holes in each column t is t=1, t=2, and t=3;
[0035] Figure 7 The distribution diagram of flame temperature at 30ms under the conditions of air explosion and filling barrier explosion-proof porous medium and the number of through holes in each column t is t=1, t=2, and t=3;
[0036] Figure 8 The flame development speed demonstration diagram at 10ms when the porous medium filled has three through holes in each row and the through hole diameters are 2.5, 3.5, and 4.5 mm;
[0037] Fig. 9 The flame development speed demonstration diagram at 30ms when the porous medium filled has three through holes in each row and the through hole diameters are 2.5, 3.5, and 4.5 mm;
[0038] Fig.10 Demonstration diagram of flame development speed at 1ms for porous media without through-holes;
[0039] Fig.11 Demonstration diagram of flame development speed at 20ms for porous media without through-holes;
[0040] Fig.12 Demonstration diagram of flame development speed at 30ms for porous media without through-holes;
[0041] Fig.13 The pressure distribution diagram of the flame at 30ms when the porous medium is filled with three through holes in each column;
[0042] Fig.14 The pressure distribution diagram of the flame at 30ms when the porous medium is filled with two through holes in each column;
[0043] Fig.15The pressure distribution diagram of the flame at 30ms when each column of the porous medium filled has one through hole;
[0044] Fig.16 This is the pressure distribution diagram of the flame at 30ms when the porous medium is filled without through holes. DETAILED DESCRIPTION
[0045] In order to make the contents of the present invention more clearly understood, the present invention is further described in detail below based on specific embodiments in conjunction with the accompanying drawings.
[0046] In the figure, 1, honeycomb mesh structure; 11, honeycomb hole; 2, through hole; a, ignition area; b, porous medium area; c, empty area.
[0047] Embodiment 1:
[0048] A barrier explosion-proof porous medium, whose components, measured by weight percentage, are: 60.0% polypropylene (Sinopec Shanghai M250E), 5% styrene-butadiene copolymer, 20% (coupling agent modified silica and carbon black and antistatic agent 1800 mass ratio 15:1), 5% decabromodiphenyl ethane, 5% aluminum hydroxide, 3% maleic anhydride grafted polypropylene, 1.7% stearic acid monoglyceride, and 0.3% antioxidant 1010.
[0049] S1. First, silicon dioxide and carbon black (mixed in a mass ratio of 3:1) and silane coupling agent KH-550 are mixed and modified in a solvent at 80°C, and the amount of silane coupling agent is 5%. Modified silicon dioxide and carbon black are obtained by centrifugation, washing and drying, and are set aside; polypropylene, modified silicon dioxide and carbon black, antistatic agent 1800, decabromodiphenylethane and aluminum hydroxide are mixed, and put into a high-speed mixer, and stirred evenly at a temperature of 125°C;
[0050] S2, then add stearic acid monoglyceride and maleic anhydride grafted polypropylene, then heat to 150°C, stir evenly, add styrene-butadiene copolymer, continue heating and stirring evenly;
[0051] S3. After stirring, transfer to a screw extruder, the extrusion temperature is 185-200°C, the mold temperature is 190-220°C, a honeycomb structure mold is set at the outlet of the extruder barrel, and the extruded pipe is vacuum cooled and shaped, cooled and shaped in a water tank, towed, and cut to obtain a barrier explosion-proof porous medium.
[0052] The barrier explosion-proof porous medium is a honeycomb mesh structure 1, which is extruded by an extruder. The extruder extrudes long strips and cuts them into required sizes to obtain a porous medium. The barrier explosion-proof porous medium has the following dimensions: the diameter of the overall inscribed circle of the porous medium is 40 mm; the side length of each hexagon inside the honeycomb is about 4.0 mm; and the wall thickness is 0.2 mm.
[0053] Embodiment 2:
[0054] A barrier explosion-proof porous medium, whose components, measured by weight percentage, are: 55.0% polypropylene (Sinopec Shanghai M250E), 10% ethylene-octene copolymer, 18% (coupling agent modified carbon black and Hoda antistatic agent 129V mass ratio of 10:1), 5% ammonium polyphosphate, 5% zinc borate, 5% maleic anhydride grafted polypropylene, 1.9% oleic acid amide, and 0.1% antioxidant 1010.
[0055] S1. First, carbon black and silane coupling agent KH-550 are mixed and modified in a solvent at 80°C, and the amount of silane coupling agent is 5% of the mass of carbon black. The modified carbon black is obtained by centrifugation, washing and drying, and is set aside; polypropylene, coupling agent modified carbon black, Heda antistatic agent 129V, ammonium polyphosphate and zinc borate are mixed, put into a high-speed mixer, and stirred evenly at a temperature of 125°C;
[0056] S2, then add oleic acid amide and maleic anhydride grafted polypropylene, then heat to 140 ° C, stir evenly, add ethylene-octene copolymer, and continue to stir evenly;
[0057] S3, after stirring, transfer to the screw extruder, the extrusion temperature is 185-200℃, the mold temperature is 190-220℃, the honeycomb structure mold is set at the exit of the extruder barrel, melt extrusion molding, the extruded pipe is vacuum cooled and shaped, cooled and shaped in a water tank, towed, and cut to obtain a barrier explosion-proof porous medium. The dimensions of the barrier explosion-proof porous medium are: the diameter of the overall inscribed circle of the porous medium is 40mm; the side length of each hexagon inside the honeycomb is about 4.0mm; the wall thickness is 0.2mm.
[0058] Embodiment 3:
[0059] A barrier explosion-proof porous medium, whose components, measured by weight percentage, are: 60.0% polypropylene (Sinopec Shanghai M250E), 5% ethylene-octene copolymer, 20% (coupling agent modified carbon black and octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate mass ratio of 15:1), 5% decabromodiphenyl ethane, 5% red phosphorus, 3% maleic anhydride grafted polypropylene, 0.9% ethylene bisstearic acid amide, and 0.1% antioxidant 1010.
[0060] S1. First, carbon black and silane coupling agent KH-550 are mixed and modified in a solvent at 80°C, with the amount of silane coupling agent being 5% of the mass of carbon black. The modified carbon black is obtained by centrifugation, washing and drying, and is set aside. Polypropylene, coupling agent-modified carbon black, octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate, decabromodiphenylethane and red phosphorus are mixed, put into a high-speed mixer, and stirred evenly at a temperature of 120°C.
[0061] S2, then add ethylene bisstearamide and maleic anhydride grafted polypropylene, then heat to 150°C, stir evenly, add ethylene-octene copolymer, and continue to stir evenly;
[0062] S3, after stirring, transfer to the screw extruder, set the temperature to 185-200℃, the mold temperature to 190~220℃, set the honeycomb structure mold at the exit of the extruder barrel, melt extrusion molding, vacuum cooling and shaping of the extruded pipe, cooling and shaping in a water tank, pulling, cutting, and obtaining a barrier explosion-proof porous medium. The barrier explosion-proof porous medium has the following dimensions: the diameter of the overall inscribed circle of the porous medium is 40mm; the side length of each hexagon inside the honeycomb is 4.0mm; and the wall thickness is 0.2mm.
[0063] The detection performance of Examples 1-3 is shown in Table 1.
[0064] Table 1:
[0065]
[0066] The testing standard for volume resistivity is GB / T1410; the testing method for flame retardancy is UL-94; the testing standard for vibration test debris is JT / T 1046-2016.
[0067] Compatibility test method: On the premise that the void rate is not more than 8%, the barrier explosion-proof material is loaded into the storage tank; one-third volume of M85 methanol gasoline is added, and the M85 methanol gasoline storage tank without barrier explosion-proof material is used as a blank test. It is stored at a temperature of 50°C for 30 days, and the change in the compression strength performance of the barrier explosion-proof material before and after the test, as well as the appearance and color changes of the storage medium are tested.
[0068] Embodiment 4-7:
[0069] The difference between Example 4 and Example 2 is that the source of polypropylene is studied and the influence on the performance is studied. The rest is the same as Example 2.
[0070] Example 4 uses Daqing Refining and Chemical PPB4228.
[0071] Example 5 uses Hanwha Total Petrochemical RB200.
[0072] Example 6 uses Ningbo Formosa Plastics 3003.
[0073] Example 7 uses ExxonMobil 7032KN.
[0074] Table 2
[0075]
[0076] Embodiment 8-10:
[0077] Compared with Example 1, Examples 8-10 differ in that the influence of lubricant type on the amount of debris in vibration test is studied, and other operations are the same as Example 2.
[0078] Example 8 is polyoxyethylene stearate; Example 9 is barium stearate; Example 10 is zinc dodecyl stearate
[0079] Table 3:
[0080]
[0081]
[0082] Comparative Example 1
[0083] The difference between Comparative Example 1 and Example 2 is that the inorganic antistatic agent is not modified with a coupling agent, and other operations are the same as those in Example 2.
[0084] Table 4
[0085]
[0086] Comparative Example 3;
[0087] Compared with Example 2, Comparative Example 3 differs in that the antistatic agent is all Heda antistatic agent 129V, the dosage is the same, and the other operations are the same as Example 2.
[0088] Comparative Example 4;
[0089] Compared with Example 2, Comparative Example 4 differs in that the antistatic agent is all coupling agent-modified carbon black, the dosage is the same, and the other operations are the same as Example 2.
[0090] Table 5
[0091] Example Volume resistivity (Ω﹒cm) Tensile strength(MPa) Comparative Example 3 <![CDATA[2.9*10 8 ]]> 18.5 Comparative Example 4 <![CDATA[1.1*10 8 ]]> 23.8
[0092] Storage tank explosion test detection:
[0093] The barrier explosion-proof porous medium of Example 1 was perforated on the side, and four test conditions were tested, namely, 1 hole, 2 holes, 3 holes, and no holes were perforated in each row.
[0094] The commercial software Fluent22 was used to establish a two-dimensional turbulent combustion model in porous media, and numerical simulation of methane-air premixed combustion in porous media in closed tanks was performed. The following simulation process is combined with the explosion test of a 4.7L cylindrical sealed tank, and four test conditions are simulated: the through-hole diameter of the air explosion and filled porous media is 3.5mm, and each column has 1 hole, 2 holes, 3 holes, and no holes (no holes in Example 1). According to the actual working conditions, the tank model is modeled in icem. Figure 3 shown.
[0095] Simulation process
[0096] First, the space inside the tank is divided into the empty area C and the porous medium area B in the icem software. After the grid is divided, it is imported into fluent, and the ignition area a is set. The ignition area a is set in the empty area a for easy observation. Figure 4 As shown. Then set the material, set the tank to a methane-air mixture, and set the tank body to steel. Then set the boundary conditions, set the front and rear walls and the tank body to adiabatic walls, set the interface between the porous medium area b and the empty area c to the internal boundary, set the porous medium area b to porous medium, and then ignite in the ignition area a to observe the subsequent combustion.
[0097] Simulation results and analysis
[0098] 1. The influence of the number of openings in each row on the flame suppression effect (t = 1, 2, 3 represents the number of openings 1, 2, 3)
[0099] The development and changes of the flame at 1ms, 20ms and 30ms are shown in Figure 5-7 .Depend on Figure 5 It can be seen that within 1ms after ignition, the temperature at the ignition point rises rapidly, and the flame spreads around at a slow speed. The flame is hemispherical and the surface is relatively smooth, indicating that the flame spreads in a laminar manner at this time; the flame develops fastest during air explosion, and gradually slows down as the number of through holes in each column of the filled barrier explosion-proof porous medium increases. The main reason is that the pressure wave speed after the explosion is much faster than the flame propagation speed. It first encounters the barrier explosion-proof porous medium and is reflected, that is, part of the pressure wave propagates back in the axial direction, which will inhibit the flame wave and hinder the development of the flame wave. The more through holes in each column of the barrier explosion-proof porous medium, the more pressure waves are reflected back, the stronger the suppression of the flame wave, and the slower the flame development.
[0100] Depend on Figure 5-7It can be seen that the flame propagation in the air explosion tank is more complete than that in the tank filled with barrier explosion-proof porous media, and slows down as the number of through holes in each column of the barrier explosion-proof porous media gradually increases, indicating that the more through holes in each column of the barrier explosion-proof porous media, the better its fire barrier performance. After the flame enters the porous medium, the collision probability of free radicals and the channel wall increases. The more holes there are, the more free radicals are destroyed in the collision, and the fewer free radicals participate in the reaction; the more holes there are, the larger its specific surface area, the better the heat dissipation effect, and the lower the internal temperature; the more holes there are, the stronger the mechanical interference effect of the porous structure "skeleton". The above three points all have an inhibitory effect on the flame wave, causing the flame to develop slowly.
[0101] The effect of the number of through holes 2 on the pressure wave suppression is given by Figure 5-7 It can be seen that the pressure decreases more significantly when the number of through holes 2 increases from 1 to 2 than when it increases from 2 to 3. It can be seen that when the number of through holes 2 in each column reaches a certain level of 3, the impact of increasing the number of through holes 2 on the explosion-proof performance will decrease. Considering that too many through holes 2 will affect the manufacturing efficiency and the strength of the porous medium, the number of through holes 2 is preferably three.
[0102] 2. Effect of opening diameter on combustion and explosion
[0103] In order to continue to explore the influence of through-hole diameter on combustion and explosion, the number of holes was selected as 3 (t=3) to continue the next simulation, and the hole diameters of R=4.5mm, R=3.5mm, and R=2.5mm were selected for simulation respectively.
[0104] Depend on Figure 8 , 9 10 It can be seen that after filling the barrier explosion-proof porous medium, the pressure wave is suppressed; when the void ratio is constant, the explosion pressure increases with the increase of the aperture, indicating that when the void ratio is constant, the smaller the aperture, the better the explosion-proof performance; the pressure decreases more significantly when the aperture decreases from 4.5mm to 3.5mm than when it decreases from 3.5mm to 2.5mm, which shows that when the aperture decreases to a certain extent, the impact of further decreasing the aperture on the explosion-proof performance will become smaller. Considering that the larger the aperture, the better the heat dissipation effect, the aperture is preferably 3.5mm.
[0105] 3. Impact of non-drilling on the explosion of porous media
[0106] Figure 10-12 The development trend of the flame generated by the detonation of the non-opened porous explosion-proof medium in Example 1 before it reaches the porous medium. The flame temperatures at 1ms, 20ms, and 30ms are respectively. The non-opened porous explosion-proof medium has a lower porosity and a more complete overall structure, providing a relatively high protection rate. The development trend is similar to that of the open porous medium ( Figure 13-16There is no obvious difference in the pressure distribution of opening three holes, opening two holes, opening one hole, and opening no holes at 30ms. However, the high porosity after opening the holes can better absorb the energy generated by the detonation and prevent the shock wave from overflowing.
[0107] from Figure 13-16 It can be seen that whether or not there are holes has little effect on the pressure distribution inside the tank. The side holes can provide more channels for gas or liquid diffusion, which helps prevent the explosion from spreading to other areas.
[0108] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. An organic barrier explosion-proof porous medium, characterized in that: The organic barrier explosion-proof porous medium is composed of the following materials: 50.0-70.0 wt% polyolefin, 5-10 wt% toughening agent, 10-35 wt% composite antistatic agent, 8-15 wt% flame retardant, 1-5 wt% maleic anhydride grafted polypropylene, 0-2 wt% color powder, 0.5-2 wt% lubricant, 0.1-0.3% antioxidant; wherein the polyolefin is one or a combination of polypropylene and polyethylene; the barrier explosion-proof porous medium is a honeycomb mesh structure; the honeycomb holes of the honeycomb mesh structure are hexagonal in their axial projection; the toughening agent is styrene-butadiene copolymer or ethylene-octene copolymer; the composite antistatic agent is one or more of aluminum powder, iron powder, copper powder, silicon dioxide, graphene, carbon fiber, carbon black, calcium chloride, and inorganic antistatic materials mixed by double The modified linking agent is used in combination with an organic antistatic agent; the lubricant is one or a combination of two of stearic acid monoglyceride, oleic acid amide, polyoxyethylene stearate, and ethylene bisstearic acid amide; the organic antistatic agent is one or a combination of several of stearic acid polyethylene glycol ester, stearic acid polyglycerol ester, dodecyl sulfopropyl betaine, monopalmitic acid sorbitan ester, octadecyl dimethyl hydroxyethyl quaternary ammonium nitrate, glycerol monostearyl ester, antistatic agent 1800, and antistatic agent 129V.
2. The organic barrier explosion-proof porous medium according to claim 1, characterized in that: The flame retardant is one or a mixture of decabromodiphenylethane, antimony trioxide, aluminum hydroxide, magnesium hydroxide, zinc oxide, ammonium polyphosphate, red phosphorus, melamine, and zinc borate; and the antioxidant is antioxidant 1076 or antioxidant 1010.
3. The organic barrier explosion-proof porous medium according to claim 1, characterized in that: The barrier explosion-proof porous medium is provided with at least two rows of through holes penetrating to the center thereof in the circumferential direction; the through hole diameter is 2.5-5.0 mm.
4. The method for preparing the organic barrier explosion-proof porous medium according to any one of claims 1 to 3, characterized in that: S1. Mix polyolefin, composite antistatic agent, flame retardant and color powder, put them into a high-speed mixer, and stir them evenly at a temperature of 118-125°C; S2, then add lubricant and compatibilizer, then heat to 130~150℃, stir evenly, add toughening agent, and continue to stir evenly; S3. After stirring, the mixture is transferred to a screw extruder with an extrusion temperature of 185-200°C. A honeycomb structure mold is provided at the barrel outlet of the extruder with a mold temperature of 190-220°C. The mixture is melt extruded and formed. The extruded pipe is vacuum cooled and shaped, cooled and shaped in a water tank, pulled and cut to obtain a barrier explosion-proof porous medium.
5. The use of the organic barrier explosion-proof porous medium in barrier explosion-proof according to any one of claims 1 to 3, characterized in that: Barrier and explosion-proof porous media are added into the oil tank for barrier and explosion-proofing.
Citation Information
Patent Citations
A circular tubular explosion-proof structure and an explosion-proof barrier composite material
CN111550669B
Flame-retardant polypropylene barrier explosion-proof material, and preparation method and application thereof
CN111019239A